The Go programming language phrasebook - Chisnall, David (Addison-Wesley Professional, 2012)
The Go Programming Language Phrasebook Essential Go code and idioms for all facets of the development process This guide gives you the code “phrases” you need to quickly and effectively complete a wide variety of projects with Go, today's most exciting new programming language. Tested, easy-to-adapt code examples illuminate every step of Go development, helping you write highly scalable, concurrent software. You'll master Go-specific idioms for working with strings, collections, arrays, error handling, goroutines, slices, maps, channels, numbers, dates, times, files, networking, web apps, the runtime, and more. Concise and Accessible Easy to carry and easy to use: Ditch all those bulky books for one portable pocket guide Flexible and Functional Packed with more than 100 customizable code snippets: Quickly create solid Go code to solve just about any problem Register your book at informit.com/register for convenient access to downloads, updates, and corrections as they become available.